Impact of the presence of median arcuate ligament on biliary complications after liver transplantation. Issue 9 (21st July 2022) - Gialamas, Eleftherios; Assalino, Michela; Elkrief, Laure; Apostolidou‐Kiouti, Fani; Piveteau, Arthur; Oldani, Graziano; Compagnon, Philippe; Berney, Thierry
Abstract: Introduction: The presence of median arcuate ligament (MAL) during orthotopic liver transplantation (OLT) may cause a significant reduction in the arterial hepatic flow. The aim of the present study is to investigate the impact of MAL on biliary complications in patients who underwent OLT. Methods: We performed a retrospective case‐control study among patients who underwent OLT in Geneva University Hospital between 2007 and 2017, depending on the presence or absence of MAL. The matching was performed according to age, gender, lab‐MELD score at the time of OLT and type of donor (living or dead). The presence of MAL was assessed by an expert liver radiologist on the preoperative CT angiographic evaluation. Results: The incidence of MAL was 6.1% (19 patients). Baseline characteristics were comparable between the two groups. No significant difference in biliary complications was found between patients with and without MAL (37% and 24%, respectively). No patient presented hepatic artery thrombosis. After logistic regression, in patients with MAL, the MAL release and gastroduodenal artery preservation compared to no treatment, showed an odds ratio for post‐OLT biliary complications of 1.5 and 1.25, respectively. There was no difference in overall graft survival and in hazard for biliary complications between patients with and without MAL. Conclusion: In the present study, we did not find any difference in the prevalence of biliary and arterial complications between patients with and without MAL. The choice of MAL treatment did not influence in a significant way the overall outcome and development of complications. However, if, at the end of arterial reconstruction, the arterial flow is not adequately established, MAL needs to be treated with the least invasive technique.